How Big Data Fast Tracked Human Mobility Research and the Lessons for Animal Movement Ecology - Thums, Michele; Fernández-Gracia, Juan; Sequeira, Ana M. M.; Eguíluz, Víctor M.; Duarte, Carlos M.; Meekan, Mark G. (Frontiers in Marine Science, 2018)
The rise of the internet coupled with technological innovations such as smartphones have generated massive volumes of geo-referenced data (big data) on human mobility. This has allowed the number of studies of human mobility to rapidly overtake those of animal movement. Today, telemetry studies of animals are also approaching big data status. Here, we review recent advances in studies of human mobility and identify the opportunities they present for advancing our understanding of animal movement. We describe key analytical techniques, potential bottlenecks and a roadmap for progress towards a synthesis of movement patterns of wild animals.